2009
DOI: 10.1002/zaac.200900029
|View full text |Cite
|
Sign up to set email alerts
|

Two Alkali‐Metal Yttrium Tellurides: Single Crystals of Trigonal KYTe2 and Hexagonal RbYTe2

Abstract: While attempting to synthesize the potassium and rubidium copper diyttrium tetratellurides KCuY2Te4 and RbCuY2Te4 in analogy to CsCuY2Te4 from 1:1:4‐molar mixtures of the elements (copper, yttrium and tellurium) with an excess of KBr or RbBr as flux and potassium or rubidium source, brown plate‐shaped crystals of KYTe2 and RbYTe2 with triangular cross‐section were obtained instead after 14 days at 900 °C in torch‐sealed evacuated silica tubes. These new ternary yttrium tellurides crystallize in the trigonal (K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The major A/RE/Q structure types have been shown in Figure , which has nicely displayed a correlation between the structure and the A/RE atomic ratio. As discussed briefly in the Introduction, as the A/RE atomic ratio increases from 0.14 (Cs[Lu 7 Q 11 ]) to 1 (AREQ 2 type ), the structure varies from a closed cavity structure to an open channel structure and then to a 2D layered structure. Such a trend goes roughly monotonically with the density decrease (identity of atom should be taken into account).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The major A/RE/Q structure types have been shown in Figure , which has nicely displayed a correlation between the structure and the A/RE atomic ratio. As discussed briefly in the Introduction, as the A/RE atomic ratio increases from 0.14 (Cs[Lu 7 Q 11 ]) to 1 (AREQ 2 type ), the structure varies from a closed cavity structure to an open channel structure and then to a 2D layered structure. Such a trend goes roughly monotonically with the density decrease (identity of atom should be taken into account).…”
Section: Resultsmentioning
confidence: 99%
“…Ternary alkali metal/rare earth metal/chalcogenide compounds (A/RE/Q, Q = S, Se, Te) are fascinating for their complexity and beauty. Up until now, eight types of structures are known and are listed according to their A/RE/Q stoichiometries as following, 1:1:2 (including about 40 compounds, e.g., RbLaSe 2 ), 3:7:12 (adopted by roughly 10 compounds, e.g., Rb 3 Yb 7 Se 12 ), 1:3:5 (only 2 examples of CsEr 3 Se 5 and CsHo 3 Te 5 ), 3:11:18 (only found in Cs 3 Tm 11 Te 18 ), 1:5:8 (RbSc 5 Te 8 ), 2:24:36 (as found in a Tm fractional occupied example, K 2 Tm 23.33 S 36 ), 1:1:4 (including 12 compounds, e.g., KCeSe 4 ), and 1:3:8 (including 4 compounds, e.g., KPr 3 Te 8 ). ,, Note that 1:1:4 and 1:3:8 types of compounds possess Q–Q bonding interactions and are thus excluded from the structure discussion below. Another exception is K 2 Tm 23.33 S 33 in which two types of building units are found as TmS 6 and TmS 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The same reaction in the absence of the flux resulted in a product with the same composition, however in the form of smaller single crystals. Babo et al reported on the synthesis of the ternary tellurides RbSc 5 Te 8 , KYTe 2 , and RbYTe 2 that were prepared using KBr and RbBr as reactive fluxes at 900°C (Babo and Schleid, 2008 , 2009 ). A study on the crystal growth of photoluminescent Pb 2 P 2 S 6 in KI at 800°C and LiBr/KBr at 500°C fluxes revealed different particle morphologies of the final products as a function of the flux used (Zhang et al, 2014 ).…”
Section: Chalcogenidesmentioning
confidence: 99%
“…Thallium chalcogenides Tl 2 Q and halides Tl X ( Q = S, Se, Te; X = F, Cl, Br, I) have several polymorphic modifications1–6 and many similarities are found between alkali‐metal and thallium compounds 7–9. With the help of reactive halide flux synthetic methods many intriguing multinary lanthanide chalcogenides have been prepared 10–12. Moreover, because thallium is heavier than any stable alkali metal and is more electronegative, its presence in a compound can modify thermal conductivity properties and stability in moist air compared to alkali‐metal analogues 13.…”
Section: Introductionmentioning
confidence: 99%